HERPES ZOSTER PADA ANAK LAKI-LAKI USIA 12 TAHUN DENGAN RIWAYAT VARICELLA: LAPORAN KASUS - Lintang Lestari; Tutik Ernawati (CV. Jasa Sukses Abadi, 2026)
Herpes zoster is a disease caused by the reactivation of latent Varicella Zoster Virus (VZV) following primary varicella infection. Although it is more commonly found in older adults, herpes zoster may also occur in children, although relatively rarely. We report the case of a 12-year-old boy who presented with grouped fluid-filled vesicular lesions accompanied by pain, burning sensation, and pruritus on the left posterior thoracic region for three days prior to admission. The patient had a history of varicella infection one year earlier. Physical examination revealed clustered vesicles on an erythematous base distributed unilaterally along the thoracic dermatome, leading to a clinical diagnosis of herpes zoster. The patient was treated with oral acyclovir, topical acyclovir, symptomatic therapy, and education for both the patient and family. Herpes zoster in children is an uncommon manifestation of VZV reactivation, particularly in immunocompetent individuals. Early diagnosis and prompt antiviral therapy play important roles in accelerating lesion healing, reducing symptoms, and preventing complications. In this case, the patient showed good clinical improvement without complications. This case highlights the importance of early recognition and appropriate comprehensive management of herpes zoster in children to achieve optimal clinical outcomes.